2018
DOI: 10.1016/j.celrep.2018.04.050
|View full text |Cite
|
Sign up to set email alerts
|

The Autism-Related Protein CHD8 Cooperates with C/EBPβ to Regulate Adipogenesis

Abstract: The gene encoding the chromatin remodeler CHD8 is the most frequently mutated gene in individuals with autism spectrum disorder (ASD). Heterozygous mutations in CHD8 give rise to ASD that is often accompanied by macrocephaly, gastrointestinal complaints, and slender habitus. Whereas most phenotypes of CHD8 haploinsufficiency likely result from delayed neurodevelopment, the mechanism underlying slender habitus has remained unknown. Here, we show that CHD8 interacts with CCAAT/enhancer-binding protein β (C/EBPβ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Second, CHD8 directly regulates CCAAT/enhancer‐binding protein B (C/EBPB) and peroxisome‐proliferator‐activated receptor (PPARγ) during adipogenesis. Loss‐of‐function mutations of Chd8 in mice were associated with impaired adipogenesis and emaciation which mimics the lean body habitus of the presently reported patient 7 . Vascular events, which are the most serious complications of Marfan syndrome, were not present in either the patient reported herein or other reported patients with CHD8 pathogenic variants.…”
Section: Figuresupporting
confidence: 62%
“…Second, CHD8 directly regulates CCAAT/enhancer‐binding protein B (C/EBPB) and peroxisome‐proliferator‐activated receptor (PPARγ) during adipogenesis. Loss‐of‐function mutations of Chd8 in mice were associated with impaired adipogenesis and emaciation which mimics the lean body habitus of the presently reported patient 7 . Vascular events, which are the most serious complications of Marfan syndrome, were not present in either the patient reported herein or other reported patients with CHD8 pathogenic variants.…”
Section: Figuresupporting
confidence: 62%
“…The expression pattern of Chd8 is thus roughly concordant with the development of specific cell types in the cerebral cortex during embryogenesis, whereas Chd8 expression and cellular development in the cerebellum largely take place in the first 2 weeks after birth. CHD8 is a key regulator of cellular differentiation, including that of cortical progenitors (Durak et al, 2016), oligodendrocyte precursor cells (Zhao et al, 2018;Marie et al, 2018;Kawamura et al, 2020), and adipocytes (Kita et al, 2018), with the upregulation of Chd8 expression during differentiation being essential for modulation of local chromatin conformation and expression of developmentally important genes. We have now shown that CHD8 is required for the proliferation and differentiation of GNPs, with CHD8 increasing the accessibility of chromatin at neuronal gene loci and thereby activating the expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…FAIRE FAIRE analysis was performed as previously described (Simon et al, 2012;Kita et al, 2018). In brief, nuclear extracts of male and female mouse cerebellum at P7 were fixed with formaldehyde at a final concentration of 1.0%, suspended in FAIRE buffer [50 mM Tris-HCl (pH 8.0), 10 mM EDTA, 1% SDS, aprotinin (10 mg/ml), leupeptin (10 mg/ml)], incubated for 10 min on ice, and subjected to ultrasonic treatment with the use of a Diagenode Bioruptor.…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…Interestingly, in one study, the fecal stercobilin level was significantly lowered (by 40%-45%) in autism spectrum disorder (ASD) model mice compared with sex matched controls 25 . Additionally, deletion of Chd8, a gene responsible for ASD, induced not only delayed the neurodevelopment directly associated with major ASD symptoms, but also induced slender habitus via inhibition of C/EBPβ-regulating adipogenesis 26 . These findings suggest that stercobilin is involved in obesity/diabetes mellitus through not only proinflammatory activities but also lipid metabolism in the C/EBPβ pathway.…”
Section: Discussionmentioning
confidence: 99%